THE PRINCIPLE OF NEUTRALITY AT SEA AFTER UN CHARTER AND UNCLOS 1982 - Enny Narwati (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2017)
The purpose of this paper is to analyze an implementation of neutrality principles at sea in time of armed conflict. It because the law of neutrality at sea has not progressed and seem stagnant since 1907 on the Hague Convention. Indeed, the UN Charter and UNCLOS 1982 set up significant developments on international law. On the other hand, there still found a lack of rules available in particular area, therefore international community provide San Remo Manual 1994. The San Remo Manual created based on the Hague Convention of 1907, the UN Charter, UNCLOS 1982, other international treaties and customary international law. To conclude, that the law of neutrality at sea should respected the sovereignty of neutral countries